A study on the awareness of e-commerce amongst the Bachelor of Accountancy students in public universities in Klang Valley / Siti Noor Hayati Mohamed Zawawi, Sharifah Norzehan Syed Yusuf and Norziaton Ismail Khan - Mohamed Zawawi, Siti Noor Hayati; Syed Yusuf, Sharifah Norzehan; Ismail Khan, Norziaton (Faculty of Accountancy, 2004)
This study is to find the students' awareness on e-commerce, and the focus is on students pursuing Bachelor of Accountancy in Klang Valley universities. Questionnaires were distributed and only 551 out of 1000 responded. The data were analysed using Statistical Package for Social Science (SPSS) version 11.5. The statistical analyses that were used are descriptive statistics, frequencies, one tail t-test, chi-square, one-way ANOVA, and Pearson Chi-Square test.